O ensino domiciliar: um movimento de relações socioeducativas com a crise da escola? - Gröhs, Karla Isabel da Costa (2022)
This master’s dissertation is part of the research line “Sociedade, Conhecimento e Educação” and was developed with the support of Research Group “Representações, Espaços, Tempos e Linguagens em Experiências Educativas” (RETLEE). The research has as object of study homeschooling. The practice consists of teaching of school-age people directly assumed by parents or guardians, who do so at home to the detriment of enrolling them in an educational institution, public or private. The movement for homeschooling gained strength in the 1960s and 1970s in the United States of America, arriving in Brazil, under American influence, around the 1980s. This is a period marked by the crisis of globalized capitalism and, consequently, of a crisis of legitimacy of the mass school. The Brazilian movement for homeschooling gained space and relevance especially after the rise to power of President Jair Bolsonaro, since, among his campaign promises, was the legalization of homeschooling in the country. From the survey of scientific research conducted in Brazil involving the theme, it was possible to notice that some aspects were widely discussed, however, the origin of homeschooling in its relationship with the school crisis was not sufficiently contemplated in the academic field. Our objective, therefore, is to analyses the relationship of interdependence between the movement for homeschooling and the school crisis through qualitative research that counts on the theoretical-bibliographic survey as a strategy. As a research method, we adopted historical-dialectical materialism. At first, we turn our gaze to the American reality of homeschooling in order to understand in what period, context and under what influences the movement for home education gained strength in that country. In a second moment, we analyse the Brazilian reality of homeschooling, as well as ideological issues involving the theme. After that, we deal with the crisis of the mass school triggered in the late 1960s and early 1970s and the economic and social context in which it was inserted. Finally, we approach the main theorists critical to the school of that period seeking to relate them to the basis of the movement for home education. Through the research it was possible to apprehend that the school crisis, especially of the school critics in crisis of the 1960s and 1970s, can be related to the movement for homeschooling in its theoretical basis due to contemporaneity, similarity and, in some cases, direct influence. Part of the theorists approached pointed out limitations in the school, however did not propose alternatives or even solutions to their ills and may, therefore, have left a gap that was filled by private alternatives such as homeschooling. The school is fundamental in the construction of a democratic society. With our research we seek to collaborate in the construction of strategies for strengthening the school through the understanding of the movement for homeschooling as another way to privatize education.